Frontline Science: COVID‐19 infection induces readily detectable morphologic and inflammation‐related phenotypic changes in peripheral blood monocytes - Zhang, Dan; Guo, Rui; Lei, Lei; Liu, Hongjuan; Wang, Yawen; Wang, Yili; Qian, Hongbo; Dai, Tongxin; Zhang, Tianxiao; Lai, Yanjun; Wang, Jingya; Liu, Zhiqiang; et al. (Journal of leukocyte biology, 2021)
Excessive monocyte/macrophage activation with the development of a cytokine storm and subsequent acute lung injury, leading to acute respiratory distress syndrome (ARDS), is a feared consequence of infection with COVID‐19. The ability to recognize and potentially intervene early in those patients at greatest risk of developing this complication could be of great clinical utility. In this study, we performed flow cytometric analysis of peripheral blood samples from 34 COVID‐19 patients in early 2020 in an attempt to identify factors that could help predict the severity of disease and patient outcome. Although we did not detect significant differences in the number of monocytes between patients with COVID‐19 and normal healthy individuals, we did identify significant morphologic and functional differences, which are more pronounced in patients requiring prolonged hospitalization and intensive care unit (ICU) admission. Patients with COVID‐19 have larger than normal monocytes, easily identified on forward scatter (FSC), side scatter analysis by routine flow cytometry, with the presence of a distinct population of monocytes with high FSC (FSC‐high). On more detailed analysis, these CD14+CD16+, FSC‐high monocytes show features of mixed M1/M2 macrophage polarization with higher expression of CD80+ and CD206+ compared with the residual FSC‐low monocytes and secretion of higher levels of IL‐6, IL‐10, and TNF‐α, when compared with the normal controls. In conclusion, the detection and serial monitoring of this subset of inflammatory monocytes using flow cytometry could be of great help in guiding the prognostication and treatment of patients with COVID‐19 and merits further evaluation. Graphical The presence of larger monocytes with more mature macrophage phenotype in blood drives the dysregulation of immune response in COVID‐19.